Evaluasi aktivitas penyembuhan luka fraksi ekstrak etanol daun kirinyuh (Chromolaena odorata (L.) R.M. King & H. Rob) pada luka sayat tikus putih (Rattus norvegicus) - Efendi, M. Rifqi; Elisma, Elisma; Zahira, Niken (Journal of Pharmaceutical and Sciences, 2023)
Kirinyuh (Chromolaena odorata (L.) R.M.King & H.Rob) is a plant from the Asteraceae family traditionally used for wound healing. This research aims to evaluate the wound healing activity of n-hexane, ethyl acetate, and n-butanol fractions derived from kirinyuh ethanol extract (Chromolaena odorata (L.) R.M.King & H.Rob). The study employed a post-test control group design in vivo using white rats (Rattus norvegicus) induced with a 3 cm long and 2 mm deep incision wound. The test formulations were applied twice a day in the morning and evening for 10 days at a dosage of 0.5 g per treatment. Wound healing effects were assessed based on the percentage of wound healing and histopathology of rat skin. The results indicated that all test fractions demonstrated wound-healing effects. The ethyl acetate fraction exhibited the most significant effect on incision wound healing compared to the positive control and the other two fractions, achieving a 75% wound healing percentage. Additionally, histopathological observations of rat skin revealed improved collagen content and epithelial cell thickness in the ethyl acetate fraction. Therefore, the ethyl acetate fraction holds the potential for development as a topical formulation in wound healing.